2014
DOI: 10.1016/j.bjorl.2014.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of evidence on the association between personality and tinnitus

Abstract: Some personality traits, especially neuroticism, psychasthenia, and schizoid aspects, may be associated with tinnitus perception and with the annoyance due to this symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
9
0
2
Order By: Relevance
“…Personality traits are psychological constructs that describe individual differences in perception, experience, emotion, cognition, and behavior on selected parameters. Personality factors could either render an individual vulnerable to developing tinnitus (e.g., Mucci et al, 2014), or facilitate the development and experience of psychological distress that, upon the perception of a tinnitus sound, extends toward the tinnitus percept (Peerenboom et al, 2015). Investigating personality factors bears high importance for understanding all psychological components of tinnitus-related distress and its maintenance, as personality may affect both exposure and reactivity to stressful events as well as differential choices of coping efforts and their differential effectiveness (Bolger and Zuckerman, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality traits are psychological constructs that describe individual differences in perception, experience, emotion, cognition, and behavior on selected parameters. Personality factors could either render an individual vulnerable to developing tinnitus (e.g., Mucci et al, 2014), or facilitate the development and experience of psychological distress that, upon the perception of a tinnitus sound, extends toward the tinnitus percept (Peerenboom et al, 2015). Investigating personality factors bears high importance for understanding all psychological components of tinnitus-related distress and its maintenance, as personality may affect both exposure and reactivity to stressful events as well as differential choices of coping efforts and their differential effectiveness (Bolger and Zuckerman, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Durai and Searchfield (2016) showed that tinnitus-related distress was associated with high neuroticism, low extraversion, high stress reaction, higher alienation, lower social closeness, lower well-being, lower self-control, lower psychological acceptance and presence of a type D personality, i.e., a tendency toward negative affectivity and social inhibition, and externalized locus of control. Moreover, several studies reported positive relations between tinnitus-related distress and a subset of "Big-Five" personality traits, namely low agreeableness, low extraversion and high neuroticism (Langguth et al, 2007;McCormack et al, 2014;Mucci et al, 2014;Dehkordi et al, 2015). Welch and Dawes (2008) stated alongside Durai et al (2017) that compared to non-tinnitus control groups, tinnitus patients were more socially withdrawn, reactive to stress, and alienated as well as less self-controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Depression and anxiety are significant factors in our understanding of differences in tinnitus symptomatology 12,13 . Personality traits, especially neuroticism, psychasthenia and schizoid traits have been associated with tinnitus perception 14 and neuroticism is known to correlate strongly with symptoms of general distress or negative affectivity 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, psychiatric parameters, such as Beck depression or anxiety scores, are closely associated with perceived tinnitus severity . From a psychological aspect, personality traits – such as neuroticism, psychasthenia, schizoid aspects and type D personality – have been reported to be related to severe tinnitus, because subjects with these personality traits usually overreact to many stimuli or exaggerate the difficulty of their situation …”
Section: Description Of Temperament and Character Traitsmentioning
confidence: 99%